From Screening To Intervention: Healthcare Team Perspectives On Integrating Social Needs Assessment Into Clinical Workflows (The Review of Diabetic Studies, 2024)
This study examines healthcare team perspectives on integrating social determinants of health (SDoH) screening and intervention into clinical workflows. Despite growing recognition that social factors significantly impact health outcomes, healthcare organizations face substantial challenges implementing systematic approaches to identify and address patients' social needs. Drawing on recent research and implementation experiences, we explore the evolution of SDoH screening from pilot programs to more comprehensive initiatives, analyzing the perspectives of diverse healthcare team members including clinicians, clinical assistants, care managers, and community health workers. Key implementation considerations include selection of appropriate screening tools, workflow integration strategies, role delineation, response protocols, and partnerships with community-based organizations. The article highlights successful approaches to balancing screening depth with clinical efficiency, addressing privacy and ethical concerns, and developing sustainable models for intervention. Recent policy developments, including changes to Medicare payment systems that recognize the impact of social factors on healthcare resource utilization, create new opportunities for sustainable implementation. By understanding healthcare team perspectives and incorporating their insights into program design, organizations can develop more effective approaches to addressing social determinants, ultimately improving patient outcomes and advancing health equity.